The Matrix of Modernism : Pound, Eliot, and Early Twentieth-Century Thought - Schwartz, Sanford, 1948- (Book collections on Project MUSE., 1985)
Sanford Schwartz situates Modernist poetics in the intellectual ferment of the early twentieth century, which witnessed major developments in philosophy, science, and the arts. Beginning with the works of various philosophers--Bergson, James, Bradley, Nietzsche, and Husserl, among others--he establishes a matrix that brings together not only the principal characteristics of Modernist/New Critical poetics but also the affiliations between the Continental and the Anglo-American critical traditions. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.